A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)
Code: La création musicale au Québec

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)
Publisher: Circuit, musiques contemporaines

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)
Code: La création musicale au Québec